Analysis of Outcomes of Surgery for Chronic Pancreatitis according to International Study Group for Pancreatic Surgery Reporting System - Kandel, Bishnu Prasad; Bista, Nimesh; Lakhey, Paleswan Joshi; Pradhan, Sumita; Maharjan, Narendra; Sharma, Deepak; Koirala, Nishnata; Bhandari, Ramesh Singh (Journal of Institute of Medicine Nepal, 2025)
Introduction Due to lack of standard reporting system for chronic pancreatitis that could include all the aspect of the disease process. International Study Group for Pancreatic Surgery (ISGPS) formulated a framework for reporting the surgery for chronic pancreatitis. This framework incorporates our recent understanding, management and outcomes of chronic pancreatitis. We aimed to report surgery performed at our department for chronic pancreatitis with this standard reporting system. Methods From January 2021 to December 2024, 32 patient who underwent surgery for chronic pancreatitis were enrolled in the study. Patients details of clinical baseline prior to surgery, morphology of diseased pancreas, type of surgery and post operative outcomes were evaluated and reported according to four domains of ISGPS. Results A total of 32 patients underwent surgery. Alcohol was the etiology in six (18.75 %) and rest were identified as idiopathic. Diabetes was prevalent in 13 (40.6%) of patient with exocrine insufficiency in only one patient. All patient had parenchymal calcification. Ductal stone was present in 29 (90.6%) with stricture in 16 (50.0%) patients. Longitudinal pancreatojejunostomy with partial pancreatic head resection was the most common surgery performed in 27 (84.3%) patients. Postoperatively two patients had major complications. There was no 90 days re-operation and mortality. Conclusion This reporting system is feasible to report surgery for chronic pancreatitis. However, large scale prospective study validation is required.